2005
DOI: 10.1111/j.1005-295x.2005.00025.x
|View full text |Cite
|
Sign up to set email alerts
|

Vertical and seasonal distribution of flying beetles in a suburban temperate deciduous forest collected by water pan trap

Abstract: Vertical and seasonal distributions of flying beetles were investigated in a suburban temperate deciduous forest in Kanazawa, Japan using water pan traps to determine the abundance and composition among vertical strata, change in the abundance and composition through seasons and determinant factors in generating the distributions. Traps were placed at three levels (0.5 m, 10 m, and 20 m above ground) on a tower. Samplings were carried out seasonally from May to November in 1999 and 2000. Variations in the abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 19 publications
3
25
0
1
Order By: Relevance
“…Our results are supported by a previous study, which reported that early occurrence of herbivores is due to preference of young leaves and availability of food resources (Leksono et al 2005). Similarly, the order of coleopteran guilds in oak forest is herbivores in May and June, scavengers in June and predators in July (Leksono et al 2005). The fact that community composition or population abundance depends on the resources available is well-known for many beetles: Ips typographus on dead wood (Økland and (Harvey et al 2008), and detritivores, predators and fungivores on quality and quantity of organic matters (Clough et al 2007).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are supported by a previous study, which reported that early occurrence of herbivores is due to preference of young leaves and availability of food resources (Leksono et al 2005). Similarly, the order of coleopteran guilds in oak forest is herbivores in May and June, scavengers in June and predators in July (Leksono et al 2005). The fact that community composition or population abundance depends on the resources available is well-known for many beetles: Ips typographus on dead wood (Økland and (Harvey et al 2008), and detritivores, predators and fungivores on quality and quantity of organic matters (Clough et al 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, July is the optimum period for herbivores. Our results are supported by a previous study, which reported that early occurrence of herbivores is due to preference of young leaves and availability of food resources (Leksono et al 2005). Similarly, the order of coleopteran guilds in oak forest is herbivores in May and June, scavengers in June and predators in July (Leksono et al 2005).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The tower was constructed of alloy metal with a height of 23 m. The mean annual air temperature in Kanazawa is 14.3°C, with the highest monthly mean temperature of 26°C (August) and the lowest of 1°C (January) (Leksono et al 2005). The vegetation around the tower is a secondary deciduous broad-leaved forest dominated by deciduous oak trees: Quercus serrata and Quercus variabilis.…”
Section: Study Site and Methodsmentioning
confidence: 99%
“…Jember (Budiarti, 2011). Hal yang sama ditunjukkan dari hasil penelitian di kanopi hutan di Jepang (Leksono et al, 2005) dan di Brasil. Di kedua lokasi jumlah spesimen yang ditemukan pada musim berbunga lebih tinggi dibandingkan non bunga (buah muda).…”
Section: Pendahuluanunclassified